Performance Evaluation of Bonding Techniques at Wireless 802.11n - Guruh Fajar Shidik; Zul Azri bin Muhamad Noh (Universitas Ahmad Dahlan, 2013)
Demands for high throughput bandwidth, encourage Point to Point wireless to serve more bandwidth for many kind application such as real-time multimedia services. We conduct research with testbed experimental at Point to Point topology use wireless 802.11n in LAB environment. The aim is to studying the performance that would be achieved by Interface Bonding and Channel Bonding techniques. We proposed experiment process and design to evaluate the performance of those techniques. Several parameters such as delay, jitter, data loss rate and throughput applied on TCP/UDP protocols with different Packet Sizes and Directional Traffic Flows. The results experiment showed that Channel Bonding has significant throughput improvement. However, the Interface Bonding results are far from expectation, we found that the performance is least than single normal link. As our finding we analyze it caused by Media Independent Interface (MII), and Scheduling Algorithm unable to work properly at wireless 802.11n using Point to Point connection.